Growth of Sustainable Enterprise Development in Entrepreneurship Based Students - Dahrul Siregar (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to analyze the appropriate model or method in developing sustainable entrepreneurship in Medan Area University students based on entrepreneurship courses This study uses a mixed method research, namely in conducting research the researcher uses a combination of quantitative methods and qualitative methods. Mixed research methods are used because in this study it produces two types of data, namely quantitative data and qualitative data.The mixed method used in this research is concurrent mixed methods, which are procedures in which the researcher brings together or combines qualitative data and quantitative data to obtain a comprehensive analysis of the research problem this research resulted decrease (reduction) in the Pre-Test value to the Post-Test Value where the Negative Ranks show an N Value of 8 and a Mean Rank of 6.06, 9 students experienced an increase in entrepreneurial learning outcomes from Pre-Test scores to Post-Test scores. The mean rank or the average increase is 11.61. Then the difference between entrepreneurial learning outcomes for the Pre-Test and Post Test, it is known that Asymp.Sig (2-tailed) is 0.185 where the value is 0.0185 <0.05, so it can be concluded that